Magnetotransport studies of SiGe-based p-type heterostructures: problems of the effective mass determination - Berkutov, I.B.; Andrievskii, V.V.; Komnik, Yu.F.; Kolesnichenko, Yu.A.; Morris, R.J.H.; Leadley, D.R.; Mironov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The Shubnikov–de Haas oscillations method of the effective mass extraction was illustrated by the magnetotransportproperties investigation of two-dimensional hole gas in Si1–xGex (x = 0.13, 0.36, 0.95, 0.98) QWs. Wehave found that for certain samples our data cannot be fitted to standard theoretical curves in which the scattering of charge carriers is described by conventional Dingle factor. It is demonstrated that reasons of deviations of the experiment from the theory are as follows; (i) influence of the spin splitting on amplitude of SdH oscillations maxima; (ii) extra broadening of the Landau levels attributed to existence of inhomogeneous distribution of thecarrier concentration; (iii) the influence of the concurrent existence of short and long-range scattering potentials; (iv) the population of second energy level in the quantum well. The ways to calculate the effective masses m* of holes in all cases are presented and values of m* are found for studied heterostructures.